Upgrading English language teaching in Iceland : guidelines and tools to motivate language teachers and students : explanatory report with ideas on how to integrate digital technology into language learning - Böðvar Dór Brynjarsson 1995- (2020)
This project is about how digital technology such as apps, internet content and video games can help both students and teachers in language learning. Technology is part of daily life; therefore, it should also have a place in teaching. The website for the project reviews useful digital tools that can make the language learning experience enjoyable. The name of the site is digital education 21 and has three main sections. They are learning characteristics of different age groups because the content of the website is suitable for students between 11 -16-year-olds. The other two sections are about language apps and video games and how teacher and students can use them in the classroom. The website includes a review of researches and academic reports about education and digital technology. The main goal of Digital education 21 is to encourage teachers to use digital tools in their teaching and to be a resource for teachers and learners who want to integrate digital technology to help in the learning process. The website:https://digitaleducation21.wixsite.com/website